Congenital Heart Disease among Down Syndrome Children at Dr. Hasan Sadikin General Hospital from 2008 to 2013 - Rajamany, Thyviyaa; Kuswiyanto, Rahmat Budi; Lubis, Leonardo (Althea Medical Journal, 2018)
Background: Children with Down syndrome are more prone to congenital heart disease due to the consequences of trisomy chromosomal 21 on gene expression. The aim of this study was to determine the pattern of congenital heart disease in children with Down syndrome. Methods: This was a retrospective study of reviewed children with Down syndrome from January 2008 to January 2013 at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. This study was conducted from August until October 2014. Patients under the age of 15 years and diagnosed having congenital heart disease from 2008 to 2013 were enrolled in this study by using the total sampling method. Incomplete medical records and children who had not performed an echocardiogram were excluded. Sex, age at diagnosis for congenital heart disease, nutritional status and other comorbidities were also examined.Results: Congenital heart disease occurred in 28 children with Down Syndrome. Patent ductus arteriosus (PDA) was the most common and found in 11 patients followed by a combination of congenital heart diseases in 5 patients. Other 3 patients had Atrioventricular septal defect (AVSD), and Tetralogy of fallot (TOF) was found in 3 patients, 2 patients had Atrial septal defect (ASD) and 1 patient had miscellaneous cardiac defect.Conclusions: The most common CHD in Down syndrome is PDA.